Sustaining Career Success: Senior Management Women Careers in the Resources Sector of Western Australia - Hopkins, Tracy Hui Ling (Curtin University, 2017)
This study explores the work experiences of thirty-one successful senior women in the resources sector of Western Australia. Career success was found to be contingent on a) believing in oneself, b) the belief of others in you, and c) overcoming barriers. Mentoring, sponsorship, professional development and networking facilitated the navigation of challenging workplace cultures. Senior women’s career success has been captured in the 3C’s Weaving Model.